System "dispersed polyvinyl acetate-calcium silicate" in furnishing materials - Petrikova, Yevgenia; Amelina, Natalia; Maistrenko, Alla; Berdnyk, Oksana (Transfer of innovative technologies, 2023)
This article focuses on the processes of interaction between calcium silicate hydrates and dispersed polyvinyl acetate in tight films with the aim of developing compounds meant for restoration and finishing works. The basis of this development relies on the concept concerning the determining role of the crystal-chemical factor of the silicate phase in the formation of organic-mineral compounds of increased durability. The characteristics of dispersed calcium silicate hydrates are portrayed. The preparation conditions, accounting for the synthesis of the product of submicrocrystalline structure, conforming with the stoichiometry CaO:SiO2=0.8-2.0 have been determined. The interaction has been studied for compounds achieved by mixing ingredients in a rapid whirling mixer, and subjected to hardening at T=20+2 °C. With the aid of XRD, DTA and Infra-Red Spectrometry methods the formation process of the sophisticated polymer silicate phase in the material was observed for a period of 90 days. The properties of the film were investigated and its high resistance against the influence of external factors was established. On this basis a conclusion concerning the quite high effectiveness of substituting portland cement with dispersed calcium silicate hydrate in polymer cement compounds has been made White colour and other various special properties determine the suitability for repair and finishing works on facades of buildings.